2022
DOI: 10.21203/rs.3.rs-1701206/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Information Management under uncertain large-scale cloud environment

Abstract: “Uncertainty” is related to working with inaccurate data, imprecise and incomplete information, and unreliable results that can lead to irrational decisions. Several approaches to managing uncertain data on the web have been proposed in the literature to resolve this problem. These approaches have failed to find the solution to this problem with accuracy and performance. Our study aims to propose a new probabilistic approach to manage web information resources in an uncertain large-scale cloud environment. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…ELM comprises attachment of outer process of glial Muller cells to one another and also to inner photoreceptor segments which has been demonstrated in animal model. 18 They revealed that tight junctions existed in the ELM between glial Muller cells and photoreceptors. Occludin was found as a key component of tight junctions.…”
Section: Role Of Outer Layers Of Retina In Pathogenesis Of Diabetic R...mentioning
confidence: 99%
“…ELM comprises attachment of outer process of glial Muller cells to one another and also to inner photoreceptor segments which has been demonstrated in animal model. 18 They revealed that tight junctions existed in the ELM between glial Muller cells and photoreceptors. Occludin was found as a key component of tight junctions.…”
Section: Role Of Outer Layers Of Retina In Pathogenesis Of Diabetic R...mentioning
confidence: 99%
“…Neutral electrolyzed water has a high oxide-reduction potential (ORP) (800 mV-900 mV) and has greater stability, allowing a longer storage time, about one year 12 . The Organic Materials Review Institute (OMRI) has listed the use of EW in crops, livestock, and surfaces 13 , this mean that it is not harmful to humans, and it is considered as environmentally friendly 14 , easy to produce and with low cost 15 . Due to the possible presence of E. coli O157:H7 in liquid egg products, the goal of the present research was to evaluate the use of the NEW as a bactericide and preservative solution, since it has previously been tested in some foods with high protein content 16,17 .…”
Section: Introductionmentioning
confidence: 99%